Internet connectivity disruption in Nicaragua (Nicaragua) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Nicaragua. Data sourced from IODA.
Network Disruption Incident ID: NI-2026-0004. Severity: critical. Confidence: 65%